2021
DOI: 10.1017/jfm.2021.780
|View full text |Cite
|
Sign up to set email alerts
|

Competing flow and collision effects in a monodispersed liquid–solid fluidized bed at a moderate Archimedes number

Abstract: We study the effects of fluid–particle and particle–particle interactions in a three-dimensional monodispersed reactor with unstable fluidization. Simulations were conducted using the immersed boundary method for particle Reynolds numbers of 20–70 with an Archimedes number of 23 600. Two different flow regimes were identified as a function of the particle Reynolds number. For low particle Reynolds numbers ( $20 < Re_p < 40$ ), the porosity is relatively low and the particle dyna… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…53 Moreover, due to non-uniform particle sizes, the fluidized bed in the P-MBR forms segregated layers of particles with larger particles (2–4 mm) located at the bottom of the bed. Yao et al 32 found that the maximum collision frequency is attained at intermediate porosity for 2 mm particles. Low porosity is characterized by more frequent weak collisions while high porosity is dominated by flow rather than collisions.…”
Section: A Case Study: Staged Anaerobic Fluidized-bed Membrane Biorea...mentioning
confidence: 97%
See 4 more Smart Citations
“…53 Moreover, due to non-uniform particle sizes, the fluidized bed in the P-MBR forms segregated layers of particles with larger particles (2–4 mm) located at the bottom of the bed. Yao et al 32 found that the maximum collision frequency is attained at intermediate porosity for 2 mm particles. Low porosity is characterized by more frequent weak collisions while high porosity is dominated by flow rather than collisions.…”
Section: A Case Study: Staged Anaerobic Fluidized-bed Membrane Biorea...mentioning
confidence: 97%
“…The hydrodynamics of fluidized-bed reactors have been investigated experimentally 28,29 and with simulations, 30–34 but membrane bioreactor studies of microbial activity have largely focused on experimental testing. 35,36 These studies do not track particle dynamics at high volume fraction (low porosity), but instead focus on macroscopic behavior such as fluidization stability and expansion.…”
Section: A Case Study: Staged Anaerobic Fluidized-bed Membrane Biorea...mentioning
confidence: 99%
See 3 more Smart Citations